Can Business Ethics be Trained? A Study of the Ethical Decision-making Process in Business Students - Ritter, Barbara A. (Journal of business ethics, 2006)
The purpose of this paper is to examine the various guidelines presented in the literature for instituting an ethics curriculum and to empirically study their effectiveness. Three questions are addressed concerning the trainability of ethics material and the proper integration and implementation of an ethics curriculum. An empirical study then tested the effect of ethics training on moral awareness and reasoning. The sample consisted of two business classes, one exposed to additional ethics curriculum (experimental), and one not exposed (control). For the experimental group, ethics exercises and discussion relevant to each topic were completed. Findings suggested gender differences such that, relative to other groups, women in the experimental group showed significantly improved moral awareness and decision-making processes. An explanation of the underlying cognitive processes is presented to explain the gender effect.